Hospital–pharmacy cooperative training and drug-taking compliance in outpatients with chronic pain: a case–control study - Uejima K; Hayasaka M; Kato J; Sakata W; Otsuka S; Watanabe F; Yoshida Y; Kamei M (Dove Medical Press, 2019)
Kentaro Uejima1,2 Masatoshi Hayasaka,1 Jitsu Kato,3 Wakako Sakata,1 Susumu Otsuka,1 Fumiyuki Watanabe,2 Yoshikazu Yoshida,1 Miwako Kamei21Department of Pharmacy, Nihon University Itabashi Hospital, Tokyo, Japan; 2Nihon University School of Pharmacy, Funabashi-shi, Chiba, Japan; 3Department of Pharmacy, Nihon University Itabashi Hospital, Tokyo, JapanPurpose: Chronic pain is a common symptom that is suffered by 20% of the overall population in Japan. Although pharmacotherapy is critical for the treatment of chronic pain, there are no reports on the pharmacies. In the present study, we examined the effect of hospital–community pharmacy cooperative training on improving drug-taking compliance, pain relief, anxiety, insomnia, and motor function in patients with chronic pain.Patients and methods: The subject sample included 87 patients with chronic pain who were examined for the first time at the outpatient services department of Nihon University Itabashi Hospital. Patients were interviewed to obtain information regarding drugs used before and after the treatment, habitually used community pharmacies, presence of cooperative training with Itabashi Hospital, drug-taking compliance, and side effects. We compared treatment outcomes before and after consultation using the Brief Pain Inventory (BPI), Hospital Anxiety and Depression Scale (HADS), EuroQol Group measure (EQ-5D) for quality of life, Athens Insomnia Scale, and Locomo 25 scale for motor function.Results: In patients who used community pharmacies that perform training, drug-taking compliance was significantly better, and a significant improvement was observed in the scores of BPI, HADS Anxiety, Athens Insomnia, and Locomo 25.Conclusion: Pharmacotherapy is essential for the treatment of chronic pain. To this end, appropriate drugs with proper drug management guidance are indispensable. In this study, the use of community pharmacies that have undergone cooperative training with hospitals improves pain and anxiety. This is achieved through proper drug management guidance, shared awareness of drug information, and achievement of better drug-taking compliance. To improve the quality of treatment for chronic pain, involvement of community pharmacies such as by providing accurate information is essential. In the future, expanding cooperative training with hospitals may further help reassure patients, facilitate drug-taking, and improve the quality of treatment for chronic pain.Keywords: chronic pain, community pharmacies training, drug management guidance, patient compliance